Misuse of technology: Factors influencing cyberloafing behavior - Nhat Tan Nguyen; Shafique Ur Rehman; Hamzah Elrehail; Hasnan Baber; Mohamed Dawood Shamout (Computers in Human Behavior Reports)
In COVID-19, information technology is a crucial source of information for transforming and expanding industries. This study explored cyberloafing behavior among workers during a job. This study hypothesized a research model by integrating the unified theory of technology acceptance and usage, the theory of planned behavior, the effort recovery model, and the general deterrence theory. A quantitative approach was used, and data were collected from 603 employees using purposive sampling. PLS-SEM was used to test the proposed hypotheses with SmartPLS. The results revealed that performance expectancy, effort expectancy, facilitating conditions, social influence, cyberloafing attitude, and website access self-efficacy significantly increased cyberloafing intention while monitoring and punishment decreased it. Moreover, psychological detachment and relaxation significantly enhanced cyberloafing behavior. Monitoring and punishment significantly decreased the intention to use cyberloafing. Finally, cyberloafing significantly increased cyberloafing behavior. The outcome of this study suggests the significant role of perception aspects of technology in determining the intention to engage in cyberloafing and enhancing the timing of Internet use. Thus, it is challenging for management to perform proper checks and balances through strong monitoring systems.